Mitos dan Pelestarian Alam: Eksplorasi Ekologi dalam Cerita Rakyat Sumber Taman Sari di Madura, Indonesia - Efendi, Agik Nur; Albaburrahim, Albaburrahim; Hamdani, Fauzul; Wafi, Abd. (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to analyze the ecological dimensions in the folklore of Sumber Taman Sari in Madura. This research employs a multidisciplinary approach, combining ecocriticism, cultural studies, environmental ethics, and folkloristics, using LÃ©vi-Strauss’ structuralism theory. Data was collected through interviews with local community leaders and field observations at the Sumber Taman Sari site. Data collection techniques included recording, note-taking, and photography. The analysis involved separating data based on the structural elements of the folklore and interpreting the ecological dimensions contained within. The findings reveal that the water source in the story is regarded as a symbol of purity and ecological balance. Prohibitions on the use of natural resources, such as trees and animals around the water source, reflect the community’s efforts to maintain ecosystem balance. Moreover, annual rituals performed at the water source reinforce the spiritual relationship between humans and nature. The folklore functions as a medium of conservation and the dissemination of local wisdom.